Capacitively sensed micromachined hydrophone with viscous fluid-structure coupling. - White, Robert D.; Cheng, Lei.; Grosh, Karl. (Tufts University. Tisch Library., 2018)
This work presents a novel design for a micromachined, capacitively sensed hydrophone. The design consists of a fluid-filled chamber constrained by two sets of membranes. The "input" membranes are arrayed around the outside of the circular chamber. Incoming sound generates a trapped cylindrical wave, creating mechanically amplified motion of the 1 mm diameter central "sensing" membrane. The membrane material is a LPCVD nitride/oxide/nitride triple-stack with respective film thickness 0.1/0.65/0.1 micron. The chamber is filled with 200 cSt viscosity silicone oil. Fluid-filling eases design constraints associated with submerging the sensor, especially with respect to exterior mass loading. Both silicon-glass anodic bonding and tin-gold solder bonding are used to form the structure, including the 5 micron sensing gap. The fluid-structure system is computationally modeled using both approximate analytic and numerical techniques. Model results indicate a 28 dB displacement gain between the motion of the "input" membranes and the "sensing" membranes. An off-chip charge amplifier, with a 10 pF integrating capacitor, is used to convert membrane motion into an electrical signal. Mean measured system sensitivity is 0.8 mV/Pa (-180 dB re 1 V/microPa) from 300 Hz-15 kHz with a 1.5 volt applied bias and a 26 dB preamplifier gain. The predicted low frequency sensitivity is 0.3 mV/Pa. The measured sensitivity exhibits considerable scatter below 7 kHz, with a standard deviation of 80%. Laser vibrometry measurements indicate that this scatter may be caused by compliance of the chip mounting scheme. Above 10 kHz, the quiescent noise is -100 dB re 1 V/rtHz. Noise characteristics exhibit a 1/f character below 10 kHz, rising to a maximum of -50 dB re 1 V/rtHz at 100 Hz. © (2005) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE) Downloading of the abstract is permitted for personal use only.